Assessment of crime prevention mechanisms in public buildings in Akwa Ibom State Of Nigeria - Ebong, S.O.; Zubairu, S.N.; Olagunju, R.E. (Penerbit Universiti Kebangsaan Malaysia, 2017)
The occurrence of crime is very rampant in the Nigerian society and its multi-dimensional nature is a threat to both national and individual security, safety and development. This paper argued that the environment and building could be designed to deter, delay, detect and deny access to unauthorised users thereby preventing crime. The research methodology adopted for the study was survey research method. Purposive sampling was used. Observation of facilities in legislative and judiciary complexes was undertaken. The findings revealed that only basic crime prevention mechanisms were applied. Critical and important anti-terrorism and high profile crime prevention mechanisms such as protective glazing, vehicle access control systems and barriers among others were not applied leaving the facilities vulnerable to criminal actions involving use of light arms. The test of hypotheses using chi-square with significance at 0.05 revealed that the application of the mechanisms depended on the type of facility. The study concluded that the public buildings and the users in the study area were not adequately secured against high profile criminal actions. It recommended appropriate upgrading of the existing facilities and use of relevant crime prevention mechanisms that can impact on terrorism and general crime prevention through proper collaboration among professional stakeholders.